Two novel golden ratio algorithms for quasimonotone variational inequalities - Li, Haiying; Wang, Xingfang (Topological Methods in Nonlinear Analysis, 2025)
In this article, we provide two viscosity-type golden ratio algorithms with different inertial terms for solving quasimonotone variational inequalities in real Hilbert spaces. Both of our algorithms use a new adaptive step size which is based on the golden ratio (5+1)/2. Under some suitable conditions, we obtain strong convergence theorems of our proposed algorithms. Moreover, several numerical results are given to illustrate the efficiency and advantages of our proposed methods.